Dataism as a New Religion? An Islamic Epistemological Critique of the Sacralization of Data in the Digital Paradigm - Hassan Anderl; Adeeb Obaid Alsuhaymi; Giullaume Heydarnia; Ledger Dhaene; Natalia Mykola Nikolaienko (Yayasan Albahriah Jamiah Indonesia, 2026)
The increasing dominance of algorithms, artificial intelligence, and big data systems in digital life has given rise to dataism as an epistemic paradigm that positions data as the primary source of truth’s legitimacy and the basis for social, economic, and moral decision-making. Studies on dataism are still largely dominated by Western epistemology and have yet to incorporate Islamic epistemology as a systematic, critical framework for data absolutization. This study aims to analyze the epistemic character of dataism and formulate an Islamic epistemological critique of the tendency to sacralize data in the digital paradigm. This research is a qualitative-conceptual study based on a literature review, using epistemological analysis, the philosophy of science, and philosophical criticism of technology approaches to dataism, alongside classical and contemporary Islamic epistemological thought. The results show that dataism constructs a reductionist knowledge structure by focusing on the validity of truth in terms of computational measurability, thereby subordinating ethical experience, rational reflection, and transcendent dimensions to algorithmic logic. This pattern produces a closed epistemic authority that functions like a secular belief system, positioning data as the final arbiter of reality and value. Islamic epistemology offers a corrective framework by integrating the senses, reason, and revelation within a hierarchy of knowledge that positions empirical data instrumentally rather than absolutely. These findings emphasize the importance of data’s epistemic boundaries and enrich the discourse on digital philosophy and technology ethics from a non-reductionist Islamic perspective.